Rancang Bangun Turbin Archimedes Screw - Sudirman, Sudirman; Setiawan, Muhammad (Faculty of Engineering, Universitas Borneo Tarakan, 2024)
Indonesia is a country that has a region rich in natural resources, including water. With the existence of this natural wealth, until now many have utilized water as a Hydroelectric Power Plant (PLTA). PLTA is a generator that utilizes potential and kinetic energy through water to produce electrical energy. This study aims to determine the Archimedes screw turbine, to obtain the results of laboratory-scale Archimedes screw turbine efficiency tests. This study uses an experimental method carried out at the Conversion Laboratory of the Mechanical Engineering Department, Borneo Tarakan University. Archimedes screw turbine with a frame length of 120 cm, width 110 cm, height 140 cm, uses a suction pump engine to suck water with a power of 5.5 HP and uses a screw with 8 threads, the turbine shaft has a shaft diameter of 10 mm with a length of 1 m, the distance between the threads is 12 cm and the inner diameter of the thread is 2.54 cm, the outer diameter is 20 cm. The highest turbine efficiency value or turbine performance is at an angle of 35o, namely 0.051% because the 35 o slope of the water pushes the screw very well so that the rotation obtained is more maximum than the 15 o and 25 o slopes.